Impact of song lyrics on pronunciation acquisiton among ESL undergraduates - Lim, Jun Jet (2024)
The purpose of this qualitative study was to see the impact of song lyrics for pronunciation acquisition among Malaysia ESL undergraduate. The research design of the study involves a pre-test, intervention, and post-test, which spans over a 7-week period. For data collection, online interviews were conducted via Microsoft Teams with a total of 8 participants from non-English speaking families who were purposively sampled. The study was focused on the minor nuances and changes in participants’ pronunciation skills, which shed lights on their progress level, challenges faced, and overall experience in using song lyrics for pronunciation improvement. Overall, although the results have shown that participants’ pronunciation was significantly influenced by song lyrics, however, due to numerous drawbacks, such as accuracy of individual sounds, omission of stress and intonation, and rhythmic nature of songs hindering the fluency of speech, the reliability and practicality of such approach remains questionable. Therefore, significant amendments have to be made in order to effectively recommend the music-based approach as an alternative approach for autonomous pronunciation learning and acquisition.